Institutional and legal framework of development of customs risk management - Halyna Razumei; Maksym Razumei; Oleksandr Huba; Viktor Kovalov; George Abuselidze; Nadiia Karpeko (E3S Web of Conferences, 2023)
The main aim of this article is to analyse the institutional and legal framework for the development of customs risk management in Ukraine on the basis of international standards and to develop proposals for its improvement. Methodological tools such as description and comparison, historical formalization, analysis and synthesis, mathematical and statistical methods for the period 2013-2020, a systematic approach, etc. were used to conduct the study. The study examines the processes of state regulation of Ukraine's foreign economic activity by managing customs risks to achieve a balance between trade facilitation and regulatory control. The development of the main elements of institutional and legal formation of the customs risk management system is analysed and the prospects of its improvement are determined. In particular, ways for improvement the effectiveness of fiscal risk management through enhanced control measures to determine the goods code, its country of origin and customs value are proposed. In addition, the authors emphasize the need to give customs authorities the right to carry out operational and investigative activities for effective security risk management.
Keywords: 330